Efficient Delivery of Triptolide Plus a miR-30-5p Inhibitor Through the Use of Near Infrared Laser Responsive or CADY Modified MSNs for Efficacy in Rheumatoid Arthritis Therapeutics - Zhang, Xiaonan; Zhang, Xin; Wang, Xipeng; Wang, Tao; Bai, Bin; Zhang, Na; Zhao, Yanjiao; Yu, Yang; Wang, Bing (Frontiers in Bioengineering and Biotechnology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease for which treatment focuses on suppressing an overactive immune system and maintaining the physiological balance of synovial fibroblasts (SFs). We found that microRNA-30-5p (miR-30-5p) was highly expressed in the rheumatoid arthritis synovial fibroblasts (RASFs) in clinical patients. Subsequently, by using the Target Scan Human 7.2 database, we predicted that phosphatidylinositol 3-kinase regulatory subunit 2 (PIK3R2) might be a putative target of miR-30-5p, a supposition verified by qRT-PCR and Western blot analyses. Recent studies have reported that PIK3R2 can maintain the physiological homeostasis of RASFs and may be a potential target in the treatment of RA.Therefore, a miR-30-5p inhibitor has potential to be used in the treatment of RA, but the low levels of miR-30-5p inhibitor internalization affects its application, and triptolide (TP) is an effective drug in the treatment of RA but induces severe toxicity and has a narrow therapeutic window. In this study, the cell internalization performance of the miR-30-5p inhibitor was improved by loading it into CADY (cell membrane penetrating peptide) modified mesoporous silica nanoparticles (MSNs), and the toxicity of TP was decreased by loading it into a controlled drug release system based on MSNs. The system was constructed by filling a phase-change materials (PCM) of 1-tetradecanol and drugs into MSNs that could be triggered by NIR laser with thermo-chemo combination RA therapy. Our results show that the miR-30-5p inhibitor loaded MSNs@CADY significantly inhibited RASF proliferation and increased apoptosis by targeting PIK3R2 to regulate the PI3K/AKT signaling pathway. In addition, MSNs@PCM@TP under 808nm laser were effective in upregulating the expression levels of protein tyrosine phosphatase nonreceptor type 22 (PTPN22) in the thymus and spleen, and downregulating the expression levels of IL-2, IL-6 and TNF-α in the serum of the RA rats. Finally, the results of the pharmacodynamic study showed that the combination of MSNs@CADY@miR-30-5p inhibitor and MSNs@PCM@TP under 808nm laser significantly increased the effectiveness of the RA treatment. These findings provide a novel understanding of RA pathogenesis and a theoretical basis for RA treatment.